From tradition to sustainability: Toraja Arabica coffee as heritage, conservation practice, and source of livelihood - Tenriawaru, A. Nixia; Darma, Rahim; Nishantha, Busige; Mohd Nawi, Nolila; Bakheet Ali, Hamed Noralla; Syam, Siti Hardiyanti; Amandaria, Riri; Azkar, Riad (Frontiers Media SA, 2026)
Toraja Arabica coffee is a globally renowned specialty product that is valued for its unique taste, cultural heritage, and ecological significance. Despite its premium reputation, the sector faces persistent challenges, such as low productivity, weak infrastructure, price volatility, and dependence on middlemen, which limit farmers’ bargaining power and income. Additionally, heritage branding risks reducing rich cultural traditions to mere marketing, while ecological pressures threaten the fragile highland ecosystems. This study explores the transition of Toraja coffee “from tradition to sustainability,” emphasizing its multifunctional role in highland communities. Using a qualitative case study approach, data were collected through interviews, focus group discussions, expert questionnaires, field observations, and secondary sources involving farmers, cooperatives, traders, SMEs, coffee shop owners, extension officers, and government representatives. The findings reveal that Toraja coffee is more than a commodity; it represents cultural identity through rituals and kinship, promotes conservation via shade-grown agroforestry, and serves as a vital livelihood source. However, structural imbalances and ecological and cultural vulnerabilities hinder long-term resilience. Strengthening cooperatives, improving infrastructure, adopting climate-smart practices, and developing balanced branding strategies are essential steps toward achieving sustainability. Toraja coffee demonstrates how cultural and ecological values can be integrated with global markets while highlighting the risks of commodification and inequality.